Wage inequality and structural change - Joanna Tyrowicz; Magdalena Smyk (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
Income inequality in the context of large structural change has received a lot of attention in the literature, but most studies relied on household post-transfer inequality measures. This study utilizes a novel and fairly comprehensive collection of micro data sets from between 1980's and 2010 for both advanced market economies and economies undergoing transition from central planning to market based system. We show that wage inequality was initially lower in transition economies and immediately upon the change of the economic system surpassed the levels observed in advanced economies. We find a very weak link between structural change and wages in both advanced and post-transition economies, despite the predictions from skill-biased technological change literature. The decomposition of changes in wage inequality into a part attributable to changes in characteristics (mainly education) and a part attributable to changes in rewards does not yield any leading factors.
Keywords: E24; D31; N34; O57; P36; P51; 330; wage inequality; structural change; transition; skill biased technological change